Government Scheme for the Development of Women Entrepreneurs in Bihar: Promoting Women's Entrepreneurship for Socioeconomic Development in Bihar (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Ladies strengthening is a piece of comprehensive advancement in Bihar just as India. Any sort of progress is a legend without considering all sexes remembering ladies for the economy. In this association assortment of limited time measure are taken in to thought in Bihar for the advancement of ladies business visionaries in Bihar just as India. So as to bear the cost of certainty to ladies ventures in the smaller than expected or little and minuscule undertakings part various recommendations have been planned by government. These proposition are focused for the advancement of ladies ventures in Bihar. Service of Human Resource Development and Department of Women and Child Development have declared the National Policy for the Empowerment of Women 2001 for usage which has recommended the objectives and destinations for the strengthening of ladies in Bihar just as in India.Women business people are a huge division of the worldwide journey for supported financial turn of events and social headway. In Bihar, however ladies have assumed a significant function in the general public, their enterprising inclination has not been fittingly tapped because of the lower status of ladies in the general public. Lately, the strengthening of lady has been recognized colossally and it is the deepest issue in deciding the situation of ladies. The National Commission for Women was set up by an Act of Parliament in 1990 to protect the rights and legitimate substances of ladies. The 73rd and 74th Amendments (1993) to the Constitution of India have given to reservation of seats in the neighborhood assemblages of Panchayats and Municipalities for ladies, establishing a solid framework for their cooperation in dynamic at the nearby levels.